(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
The selection of drill bit is an essential issue in the well planning. Furthermore, identification and evaluation of sedimentary rocks before well drilling plays a crucial role in choosing the drill bit. Moreover, the Markov chain as a stochastic model is one of the powerful methods for identifying lithological units, which is based on the calculation of the transition probability matrix or transition matrix. The Markov chain experiences transitions from one state (a situation or set of values) to another according to specified probabilistic rules. In this paper, this is the first time that the Markov chain was implemented for bit selection in a formation with different sedimentary facies (such as Dashtak formation). Therefore, proper drill bit was recommended by utilizing the transition matrix of rock facies and available bits. This process was carried out in two wells where the thicknesses of Dashtak formation are 960 meters and 1410 meters. Consequently, the results indicate that the Markov chain is a practical method for selecting bits in a sequence of rock facies based on an acceptable matching between the reality mode (the used bits in the well) and the Markov chain results. Besides, in the case of using an improper bit in a well, and using a bit in washing and reaming operation, there were differences between the real used bits and the Markov chain outputs.